Middle East respiratory syndrome: obstacles and prospects for vaccine development. (July 2015) - Papaneri, Amy B; Johnson, Reed F; Wada, Jiro; Bollinger, Laura; Jahrling, Peter B; Kuhn, Jens H
<x xml:space="preserve">Abstract</x> The recent emergence of Middle East respiratory syndrome (MERS) highlights the need to engineer new methods for expediting vaccine development against emerging diseases. However, several obstacles prevent pursuit of a licensable MERS vaccine. First, the lack of a suitable animal model for MERS complicates the in vivo testing of candidate vaccines. Second, due to the low number of MERS cases, pharmaceutical companies have little incentive to pursue MERS vaccine production as the costs of clinical trials are high. In addition, the timeline from bench research to approved vaccine use is 10 years or longer. Using novel methods and cost-saving strategies, genetically engineered vaccines can be produced quickly and cost-effectively. Along with progress in MERS animal model development, these obstacles can be circumvented or at least mitigated.